2015
DOI: 10.1210/jc.2014-2401
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Tregs in Peripheral Blood of PCOS Patients – a Consequence of Aberrant Il2 Signaling

Abstract: The study suggests that women with PCOS have reduced Tregs due to an inherent hyporesponsiveness to IL2, which is unable to activate STAT5B and reduce FOXP3 expression. IL2-based therapeutic strategies can ameliorate complications in PCOS by suppressing the AKT/PIK3 arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…Earlier reports had shown that iNOS derived NO regulates mouse oocyte maturation [37] as well as NO-Treg generation [38]. We have recently reported lowered Tregs in PCOS [39] and thus our observed low iNOS expression assumes larger significance as it would add to the burden of reduced FOXP3 expression further compromising Treg generation. eNOS expression has been shown in PBMC especially in neutrophils and monocytes [40, 41].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Earlier reports had shown that iNOS derived NO regulates mouse oocyte maturation [37] as well as NO-Treg generation [38]. We have recently reported lowered Tregs in PCOS [39] and thus our observed low iNOS expression assumes larger significance as it would add to the burden of reduced FOXP3 expression further compromising Treg generation. eNOS expression has been shown in PBMC especially in neutrophils and monocytes [40, 41].…”
Section: Discussionmentioning
confidence: 58%
“…Niedbala et al have reported NO• to induce CD4 + CD25 + Foxp3 - regulatory T cells (NO• - Tregs) with suppressive properties in peripheral blood [38]. In our previous study we showed that peripheral pool of PCOS women contained low T-regulatory cells (Tregs) [39]. This is a strong implication that lowered NOS activity on account of decreased iNOS/eNOS expression in PBMC of PCOS patients contributes to decreased NO•-Tregs and exacerbates Treg depletion due to lowered FOXP3.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a decrease of Tregs is related to the occurrence of spontaneous abortion [86], unexplained recurrent abortions [87], and preeclampsia [88]. In addition, the number of Tregs in the peripheral blood of PCOS patients was shown to be lower than that of controls [89]. Therefore, the Th17/Tregs ratio would increase, leading to a chronic inflammatory state in the ovary and throughout the body.…”
Section: Regulatory T Cells (Tregs)mentioning
confidence: 99%
“…Moreover, reduced capability of Treg generation has been found to lead to PCOS in humans and estrogen exposed PCOS mouse model. [ 8 ] CTLA4, a specific Treg markers, is an important costimulatory molecule indulged in playing suppressive function of Treg cells. Therefore, CTLA4 is supposed to affect the immune response and play roles in the pathogenesis of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, both mouse models and human study results demonstrated that reduced capability of Treg generation may possibly lead to PCOS. [ 8 ] And cytotoxic T-lymphocyte-associated antigen 4 (CTLA4) is a specific marker of Treg and can compete with CD28 to bind to CD80 and CD86 on antigen-presenting cells, such as macrophages. Through blocking the engagement of CD28 on T cells, CTLA4 can prevent T-cell activation, and thereby reducing the levels of interferon-γ, interleukin (IL)-6, and IL-1β.…”
Section: Introductionmentioning
confidence: 99%